Implementasi Ajaran Catur Guru Dalam Membentuk Karakter Anak Usia Dini di Kota Mataram - Diwyastini, Ida Ayu Kartika; Wijana, I Nyoman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Character education is very important for early childhood because it will later be applied in the community in carrying out social activities. As a phenomenon that is often seen, especially among teenagers, many children commit acts of violence, murder, do not respect their parents, hold demonstrations in the wrong way and do not comply with applicable regulations, the spiritual level of children is low and many more. This is caused by a lack of character formation from an early age because if character education is lacking from an early age then in adolescence they will be quickly affected by promiscuity or bad relationships and this can damage the future and reduce the quality of human resources. This study focuses on character formation, implementation, Tri Kaya Parisudha and early childhood. The aim of this research is to improve the quality of human resources from the implementation of the Tri Kaya Parisudha teachings. The method used in this research, namely qualitative, emphasizes analysis on deductive and inductive inference processes as well as analysis of observed phenomena using scientific logic in formal and argumentative thinking in research on the implementation of teachers' chess teachings in building the character of early childhood. If character education through the Tri Kaya Parisudha teachings can be implemented well, it can reduce cases that occur due to lack of character formation at an early age. It's different if you instill good character from an early age then it will become a habit and in adolescence you can sort out the good things and the bad things that can be imitated so that you can produce quality human resources.